Cost/benefit v perinatologii--II. Aplikace v podmínkách Ceské republiky - Stembera, Z (Ceska gynekologie, 1998)
Using western economic models evaluating cost/benefit in perinatal care, the author analyzed on examples of undesirable perinatal outcomes the health benefit as a result of extension of screening and therapeutic procedures in the Czech Republic in 1990-1996 as well as the efficacy, effectivity and efficiency of these procedures. The results of analyses provided evidence that extension of the above procedures led to a decline of undesirable outcomes, different for each of the five investigated types, but at the same time a considerable increase of costs was recorded which exceed resources available at present for health services in the Czech Republic. Further development of perinatal care which will have to overcome this discrepancy without jeopardizing the present high standard of perinatal care will have to consider a compromise which will achieve a balance between present professional knowledge and possibilities, the moral aspect, demands of society and available funds.
Keywords: Česká republika; perinatální péče; Models, Econometric; lidé; Female; Infant, Newborn; Pregnancy; analýza nákladů a výnosů; Perinatal Care; těhotenství; novorozenec; Czech Republic; ekonometrické modely; Cost-Benefit Analysis; ženské pohlaví; Humans